Therapeutic Hypothermia - Tisherman, Samuel A.; Sterz, Fritz; SpringerLink (Online service) (Boston, MA : Springer US, 2005)
The use of hypothermia for a variety of therapeutic purposes has a long and erratic history. Hypothermia was used for protection and preservation of the heart and entire organism during planned operative ischemia. Attempts were also made to use hypothermia for resuscitation from cardiac arrest and for management of head trauma. Therapeutic Hypothermia will provide a review of the subject, in particular, resuscitative hypothermia and include known mechanisms of action and results from both mechanistic and outcome laboratory studies and clinical trials. Cooling methods and potential side effects of hypothermia will be addressed as well as recommendations for future laboratory and clinical research. This volume will be of interest to both the researcher interested in therapeutic hypothermia as well as the clinician interested in the potential use of therapeutic hypothermia in their patient population. Samuel A. Tisherman is an Associate Professor in the Department of Surgery, the University of Pittsburgh, Pennsylvania, USA. Fritz Sterz is a Professor in Emergency Medicine at the University of Vienna, Vienna, Austria.
Global Brain Ischemia: Animal Studies -- Global Cerebral Ischemia: Clinical Studies -- Focal Cerebral Ischemia: Mechanisms -- Focal Cerebral Ischemia: Clinical Studies -- Traumatic Brain Injury: Laboratory Studies -- Traumatic Brain Injury: Clinical Studies -- Spinal Cord Ischemia and Trauma -- Asphyxia -- Neonatal Asphyxia -- Hemorrhagic Shock and Exsanguination Cardiac Arrest -- Adult Respiratory Distress Syndrome and Sepsis -- Liver Failure and Intracerebral Hypertension -- Myocardial Ischemia and Infarction -- Cooling Methods -- Detrimental Effects of Hypothermia -- Future Directions.
Keywords: Medicine; Critical care medicine; Medicine & Public Health; Intensive / Critical Care Medicine; Electronic books